A correlational study between the academic performance and perceived subject difficulty of selected fourth year BS Accountancy students of Pamantasan ng Lungsod ng Maynila - Canlas, Arvile Jess L.; Capayas, Levilyn Chariss G.; Creus, Donna Rose B.; Rivera, Iwi Rose B.; and Salazar, Azel Ann. C. 4 0 16; 5
u
Thesis: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2